Analisis Hukum Islam terhadap Praktik Denda Keterlambatan pada Sistem Pembayaran Paylater di E-Commerce: Studi Kasus Shopee PayLater - Velisya, Reva; Kurniawati, Fitri (JISH: Jurnal Ilmu Syariah dan Hukum, 2026)
The development of financial technology (fintech) has transformed public consumption patterns with the emergence of deferred payment features or "PayLater," such as Shopee PayLater. Although offering convenience, this practice has sparked serious debate within the perspective of Islamic economic law regarding the legality of the contract and its impact on consumer behavior. This study aims to analyze the transaction mechanism of Shopee PayLater and formulate risk mitigation solutions to ensure compliance with Sharia principles. The research method used is qualitative with a library research approach, referring to DSN-MUI fatwas and contemporary fiqh muamalah literature. The results indicate that the current Shopee PayLater mechanism contains elements of Riba Nasi'ah and Riba Jahiliyah due to the imposition of interest and penalties on top of the principal debt in the Qardh contract. As an alternative solution, this study recommends restructuring the contract into Murabahah (sale and purchase) or Ijarah (service lease) to eliminate usury elements, as well as diverting late penalty funds as social funds (qardh al-hasan). Furthermore, from the consumer side, strengthening financial literacy and cultivating the attitude of Qana'ah are necessary to mitigate impulsive behavior and debt traps. This study concludes that Islam not only prohibits usurious practices but also offers solutive pathways for the digital economic ecosystem.